Bridging the Gap: A Qualitative Study Exploring the Impact of the Involvement of Researchers With Lived Experience on a Multisite Randomised Control Trial in the National Probation Service in England and Wales - Elizabeth Simes; Stephen Butler; Elizabeth Allison; Barbara Barrett; Anthony Bateman; Angus Cameron; Mike Crawford; Alison Frater; Zoe Hoare; Mary McMurran; Paul Moran; Stephen Pilling; et al. (Health Expectations)
ABSTRACT Introduction Methodological and ethical arguments support the involvement of individuals with lived experience in research to reduce engagement barriers and ensure those directly affected by studies contribute to knowledge generation. However, there is limited evidence on the impact of including researchers with lived experience of serving a prison or community sentence in clinical trials. This qualitative study aimed to explore the value of involving researchers with lived experience of the criminal justice system as data collectors in the Mentalization for Offending Adult Males (MOAM), a multisite RCT conducted in the National Probation Service in England and Wales. Methods Semi‐structured interviews were conducted with 30 trial participants and 17 key stakeholders, either in person or via telephone. The interviews were transcribed verbatim and analysed thematically. Findings Five themes emerged for trial participants and 11 for key stakeholders. For some, lived experience researchers helped overcome engagement barriers by fostering common ground with participants who were serving a prison or community sentence during recruitment. Participants reported that the involvement of lived experience researchers enhanced the study by facilitating knowledge transfer in certain instances. However, their inclusion did not eliminate all barriers and, for some participants, introduced new challenges to engagement. Conclusion Forensic lived experience researchers bridged the gap by fostering trust between data collectors and participants. Future studies should ensure that lived experience researchers receive adequate clinical supervision to support their role. The adopted methodology challenged assumptions about knowledge generation and stereotypes associated with being an ex‐offender, benefiting both lived experience and traditional researchers. Patient or Public Contribution The study was developed in collaboration with User Voice (charity number: 1136047), who contributed to the study's design and conduct. The service user organisation co‐designed the interview schedule and directed the protocol for participant payments, emphasising a consistent approach to avoid tokenism and ensure equal recognition of all contributions. The dissemination plan was developed in partnership with individuals with lived experience of the criminal justice system.